Estimating Geothermal Energy Resource Potential within Jema’a Local Government Area of Kaduna State, Nigeria - Garba M Ephraim; Afuwai G Cyril; Mamman G Ayuba; Joseph I Abaleni (Physics Access, 2022)
This study used aeromagnetic data of Jema’a, sheet No.188 to estimate the geothermal energy resource potential in Jema’a Local Government Area of Kaduna State, Nigeria. The study area lies between latitude and N and longitude and E. Total magnetic intensity (TMI) map of the area was produced from the gridded data. Residual map was obtained by removing regional field from the TMI which was divided into 36 blocks for spectral analysis. The centroid depth (Z_0) was obtained by dividing the gradient of the lengthiest wavelength part of the spectrum by the wave number. The depth to top (Z_t) of the magnetic source was obtained from the gradient of high wave number portion of the power spectrum. The values of Z_0 and Z_t were used to obtain the values for depth to bottom of the magnetic source (Z_B). The geothermal gradient (dT/dZ) values were obtained by dividing by Z_B while the heat flow (q) values were obtained by multiplying dT/dZ by the constant k (2.51). The dT/dZ values obtained range from 13.560 to 4000.000℃/km with an average value of and having the least (13.560 ℃/km) around Kafanchan axis and the highest (4000.000 ℃/km) around Sanga. The values range from 34.036 to 1004.00 mW m^ (-2) with an average value of 118.089 mW m^ (-2). The dT/dZ values were observed to be greater than 100 mW m^ (-2) around Sanga and Andaha axes. The Curie depth (28 km) was deepest at the South-South, South-East and South-West regions. Since magnetic properties of minerals disappear at this temperature and thermal conductivity of rocks increases with depth, these areas are potential geothermal energy source.